Allowable heat load on the edge of the ITER first wall panel beryllium flat tiles. (August 2017) - Mitteau, R.; Eaton, R.; Gervash, A.; Kuznetcov, V.; Davydov, V.; Rulev, R.
Highlights: Plasma facing components (PFC) are mainly designed to receive the heat load on the top (front) face of the armour. Some heat load deposition on lateral faces is unavoidable, because of component segmentation and port opening, as well as assembly or manufacture tolerance. Surface shaping and component shadowing mitigates the edge heat load to a certain extent, but edge heat load still occur both at the global (component to component) and/or local (tile to tile) scales. This work focuses on establishing power allowable for PFC edges. This is especially critical for water cooled components that uses flat bonded armour tiles to the heat sink, for ensuring the long-term integrity of the bond. The work is done on the context of flat tile concept, for the ITER fist wall being armoured with beryllium tiles. The edge heat load allowable is based mainly on experiments, as there is no engineering recognised damage criteria for bi-metallic bonds. An edge heat load criterion of 10% of the top (front) heat load at the incident surface is proposed and demonstrated by heat flux testing. Abstract: Plasma facing components are usually qualified to a given heat load density applied at the top face of the armour tiles with normal incidence angle. When employed in tokamak fusion machines, heat loading on the tile sides is possible due to optimised shaping, that doesn't provide edge shadowing for all design situations. An edge heat load may occur both at the tile and component scales. The edge load needs to be controlled and quantified. The adequate control of edge heat loads is especially critical for water cooled components that uses armour tiles which are bonded to the heat sink, for ensuring the long-term integrity of the tile bonding. An edge heat load allowance criterion of 10% of the top heat load is proposed. The 10% criterion is supported by experimental heat flux tests.